Healthy Living: Diabetes Warning Signs - Linda B. Bobroff (EDIS)
Could you have diabetes and not know it? It is possible. More than one-fourth of the people who have diabetes don’t know they have the disease! Treating and managing diabetes greatly decreases the risk of diabetes-related health problems. Review the list of warning signs below and check any that you have experienced. This revised 2-page fact sheet was written by Linda B. Bobroff and published by the UF Department of Family, Youth and Community Sciences, July 2014.